Comparative analysis of health risk behaviours demonstrated by law students of the University of Szczecin in Poland and the University of Lund in Sweden - Kamińska, Magdalena Sylwia; Dąbrowska, Oriana; Baranowska, Ewa; Rotter, Iwona; Rozkrut, Monika (Polish Journal of Public Health, 2011)
Introduction. Lifestyle and health awareness are the factors which have the greatest and direct impact on the health of a society. Problem of risky behaviours in the teenage population is a global phenomenon showing an upward tendency. Social and health costs of risky behaviours are borne by a whole society. Aim. The aim of this study was to analyse students’ opinions about cigarette and alcohol consumption by students’ community and to investigate if the above mentioned risk behaviours are associated with the period of studying. Material and methods. The study was performed on 70 law students of the University of Szczecin in Poland and 62 law students of the University of Lund in Sweden. The method used in the study was a diagnostic survey. Results. About 24.2% of all surveyed students admit to current cigarette smoking. About 56.5% of the Polish and 64.5% of the Swedish think that smoking is detrimental to health. Some 40% of the Polish and 52.9% of the Swedish who declare smoking, either regularly or occasionally, began smoking during their studies. Moreover 58.6% of the Polish and 38% of the Swedish regard drinking alcohol as having harmful effect on health. Nevertheless, 12.8% of the surveyed Poles and 9.7% of the surveyed Swedes confess to drinking alcohol regularly. Furthermore, 3.5% of the Polish and 65% of the Swedish current alcohol users claim that the beginning of studies was a factor which contributed to their drinking alcohol. Conclusions. 1. The majority of respondents from Poland and Sweden were aware of detrimental effects of cigarette and alcohol consumption on health, but it did not motivate them to reduce the use of these stimulants. Due to health-risk behaviours, a prognosis for respondents’ health is unfavourable. 2. Most of respondents from Poland and Sweden had tried cigarettes and alcohol before they undertook their studies. 3. Cigarette and alcohol consumption did not statistically significantly correlate with the selected sociodemographic factors.